Clients with chronic conditions: community nurse role in a multidisciplinary team. Issue 5 (3rd July 2013) - Wilkes, Lesley; Cioffi, Jane; Cummings, Joanne; Warne, Bronwyn; Harrison, Kathleen
<x xml:space="preserve">Abstract</x> Aims and objectives To define and validate the role of the community nurse in a multidisciplinary team caring for clients with chronic and complex needs. Background A key factor in optimising care for clients with chronic and complex conditions in the community is the use of multidisciplinary teams. A team approach is more effective as it enables better integration of services. The role of the community nurse in the multidisciplinary team has as yet not been delineated. Design A modified Delphi technique was used in this study. Methods A group of 17 volunteer registered nurses who were experienced in the care of clients with chronic conditions and complex care needs in the community formed a panel of experts. Experts were emailed a series of three questionnaires. Results Main findings show that the role of the community nurse in a multidisciplinary team for clients with chronic conditions has six main domains – advocate, supporter, coordinator, educator, team member and assessor. Conclusion A consensus on the role of the community nurse in the multidisciplinary team is described. The six key role domains reaffirm the generic role of the nurse and the validation of the role clarifies and reinforces the centrality of the community nurse in the team. Further refinement of the community nurse role is indicated to increase comprehensiveness of role descriptors particularly for the role domain, advocate. Relevance to clinical practice Community nurses working in multidisciplinary teams caring for clients with chronic conditions can define their role as a team member. The working relationship of the community nurse with other health professionals in the multidisciplinary team as a key approach to more integrated care for clients and carers enables the use of this approach to be better understood by all team members. With this increased understanding, community nurses are in a position to build stronger and more effective care teams.